A Rare Case of Localised Isolated Penile Fournier’s Gangrene and a Short Review of the Literature - Antonios Katsimantas; Nikolaos Ferakis; Panagiotis Skandalakis; Dimitrios Filippou (Case Reports in Urology)
Penile Fournier’s gangrene (FG) is very rare clinical entity, which is also known as penile necrotizing fasciitis or wet gangrene of the penis. It is associated with increased morbidity and mortality and in the majority of the described cases it affects not only penis but also the adjacent organs and tissues (e.g., bladder, muscles, rectum, testis, and scrotum). We report a rare case of a previously healthy 68-year-old male, who presented with acute isolated penile Fournier’s gangrene. Pus culture was identified with pathogens Enterococcus faecalis, Streptococcus gordonii, and Prevotella melaninogenica. Prompt surgical exploration, fluid resuscitation, antibiotic treatment, and diligent postoperative care are the cornerstone in the successful treatment of this emergency with high mortality.